Pengaruh Metode Storytelling Terhadap Peningkatan Dorongan Bertindak Dan Efikasi Diri Dalam Melakukan Perilaku Hidup Bersih Dan Sehat - Ivony Fristy Noventy Putriningtyas; Budiman Budiman; Lina Safarina; Neti Juniarti (Universitas Pahlawan Tuanku Tambusai, 2026)
Clean and Healthy Living Behavior (PHBS) in elementary school children is a crucial foundation for shaping healthy habits from an early age. However, the low awareness of PHBS among students remains a concern in several regions, including Sorong Regency. This study aimed to determine the effect of the Storytelling method on improving cues to action and self-efficacy in practicing PHBS among students at SDN 12 Sorong Regency. The research employed a quasi-experimental design with a pretest–posttest control group approach. The sample consisted of 96 fifth-grade students, including 43 students in the intervention group and 53 in the control group, selected through total sampling. The instrument used was a PHBS questionnaire based on the Health Belief Model theory. Data were analyzed using the Wilcoxon and Mann-Whitney tests. The results showed a significant difference in cues to action and self-efficacy scores before and after the intervention in the intervention group (p < 0.05), while no significant difference was found in the control group (p > 0.05). The Mann-Whitney test also confirmed a significant effect of the Storytelling method on enhancing students' cues to action and self-efficacy in practicing PHBS (p < 0.05). In conclusion, the Storytelling method is effective in improving cues to action and self-efficacy among elementary school students in implementing PHBS. Keywords: Storytelling, cues to action, self-efficacy, PHBS, elementary school students